Green Building Assessment In Shopping Buildings - David Kiki Baringin Maruli Tua Samosir (Indonesian Management and Accounting Research, 2021)
Research on green building in terms of accounting science is still rare. This research aims to explore the benchmarks and criteria for green building in its application to multi-storey buildings and to contribute to increasing the efficiency of building operational costs.The method used in this research is through exploration of data from questionnaires collected using simple arithmetic techniques and graphic techniques in summarizing the observational data. The number of respondents who responded to the questionnaire that was run until this data was processed was 111 respondents.The results of this study indicate that the application of green building benchmarks can be said to have been implemented because the average percentage of respondents who answered Yes was 58.4% or above the standardization used in this study, namely 57% (gold rank).This research provides theoretical implications, which is able to strengthen the theory of the reliability of accounting. One of them is green accounting, which is the triple bottom line (planet, people and profit). In order that implementation of green building which has been applied only from the civil engineering condition of the building, the art of building architecture and the electrical engineering of the building, but now it has begun to be calculated regarding advantages and disadvantages similarly the benefit of the green building .From a micro economics (organizational) point of view, this research contributes to educating property business and stakeholders that green building is not object that is expensive although is a solution for cost efficiency. People can distinguish the price of green buildings and ordinary buildings.